Comparison of Sequential and Concomitant Therapy for Eradication of Helicobacter Pylori - Shabbir, Faisal; Nisar, Shazia; Ashraf, Nadeem; Khan, Babar; Hakim, Farzana; Khan, Hammad (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effectiveness of sequential and concomitant therapy for the eradication of Helicobacter pylori.Study Design: Quasi-experimental study.Setting and Duration of Study: Department of Gastroenterology and Medicine, Pak Emirates Military Hospital, Rawalpindi Pakistan from Jun to Sep 2021.Methodology: A total of 105 patients who were H-pylori positive on stool antigen tests and had to undergo eradication therapy were included in the study. Patients were randomized into Groups by lottery method. Group-A was given the Clarithromycin concomitant therapy (Omeprazole+ Amoxicillin+ Clarithromycin+ Metronidazole) for 10-14 days, while Group-B was given the Clarithromycin based sequential therapy (Omeprazole+ Amoxicillin for five days and then Omeprazole+ metronidazole+ Clarithromycin for next five days) for eradication of H pylori. A stool antigen test was done to determine the successful eradication in both Groups.Results: Out of 105 H pylori antigen-positive patients included in the study, 69(65.7%) had successful eradication of stool antigen while 36(34.3%) had stool antigen positive even after adequate treatment. The mean age of the study participants was 39.53±7.647 years. Eradication of H pylori in the study population was statistically significantly found in patients with age less than 40 years (p-value-0.033) and those who were taking sequential therapy as compared to concomitant therapy (pvalue